2008
DOI: 10.1016/j.biomaterials.2008.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting lipid raft transport with membrane targeted nanoparticles: A strategy for cytosolic drug delivery

Abstract: The ability to specifically deliver therapeutic agents to selected cell types while minimizing systemic toxicity is a principal goal of nanoparticle-based drug delivery approaches. Numerous cellular portals exist for cargo uptake and transport, but after targeting, intact nanoparticles typically are internalized via endocytosis prior to drug release. However, in this work, we show that certain classes of nanoparticles, namely lipid-coated liquid perfluorocarbon emulsions, undergo unique interactions with cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 44 publications
(64 reference statements)
2
85
0
Order By: Relevance
“…Lipids and peptides such as melittin that are inserted in the nanoparticle monolayer can then diffuse along the continuous hemifusion pore, becoming part of the target cell membrane ( Figure 6H). Entry into the cell appears to be by endocytosis of the cellular membrane to which the cargo has been transferred (22). We demonstrate that the contact-mediated transfer of melittin by nanoparticles produces cytochrome c release and apoptosis.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Lipids and peptides such as melittin that are inserted in the nanoparticle monolayer can then diffuse along the continuous hemifusion pore, becoming part of the target cell membrane ( Figure 6H). Entry into the cell appears to be by endocytosis of the cellular membrane to which the cargo has been transferred (22). We demonstrate that the contact-mediated transfer of melittin by nanoparticles produces cytochrome c release and apoptosis.…”
Section: Discussionmentioning
confidence: 89%
“…We have recently described technical details of a perfluorocarbon nanoemul-sion vesicle that appears capable of serving as a selectively targeted carrier that remains stable after insertion of melittin, which might serve to deliver the melittin in vivo (19). Our nanovehicle carriers are synthesized as an oil-in-water emulsion composed of a liquid perfluorooctyl bromide (PFOB) core having a monolayer of phospholipid forming a stabilizing interface with the aqueous media (20)(21)(22)(23)(24). We have illustrated the stable incorporation of melittin into the outer lipid monolayer of these nanovehicles by surface plasmon resonance, fluorescence, and circular dichroism spectroscopy (19).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that sulfatide served as the targeting motif that would guide the SNPs to the ECM of the tumor cells by interacting with ECM glycoproteins such as TN-C. 32 Hence, SNPs, a type of targeted NP, can deliver lipophilic drugs directly to the target cell membrane with subsequent trafficking via lipid-raft-dependent pathways. 33 The result is delivery of greater amounts of drug with more efficient and immediate access to intracellular targets. For free drug, the cell uptake mechanism is a passive diffusion process, 29 while for conventional NPs, as a nontargeted delivery system, a possible endocytosis mechanism could be involved.…”
Section: Discussionmentioning
confidence: 99%
“…PFC nanotechnology offers an approach to better select and monitor treatment in the most eligible patients as well as to deliver the targeted antiangiogenic therapy. In addition to ultrahigh payloads of paramagnetic chelates for diagnostic MR imaging, ā£ v ā¤ 3 -targeted nanoparticles can incorporate therapeutic agents for targeted drug delivery [81][82][83][84][85][86][87][88][89]. Such dual function agents may be referred to as "theranostics."…”
Section: Angiogenesis Image-guided Drug Deliverymentioning
confidence: 99%
“…Inclusion of fumagillin into the surfactant of the ā£ v ā¤ 3 -targeted fumagillin nanoparticles enables the delivery of drug into proliferating endothelial cells via "contact facilitated transport," which is promoted by the ligand-based tethering of the nanoparticle to the target cell surface and the spontaneous passive exchange of the lipid surfactant components with similar membrane lipids through hemifusion complexes [81,88,89]. The antiangiogenic effectiveness of ā£ v ā¤ 3 -targeted fumagillin nanoparticles was studied in the syngeneic Vx2 adenocarcinoma rabbit model using a minimal fraction of the TNP-470 dosages previously used in preclinical animal models [87].…”
Section: Antiangiogenic Therapy With Integrin-targeted Fumagillin Nanmentioning
confidence: 99%